Recurrent Furunculosis: incidence of anaerobes and fungi - Narain, Upma; Bajaj, Ashok Kumar; Kant, Arun (International Journal of Advances in Medicine, 2017)
Background: The occurrence of recurrent furunculosis is common. However, the only cause for the infection reported till this date was aerobes and prior reported series did not identify anaerobes as causative organisms. Methods: A retrospective study of 1760 patients with furunculosis was to determine the incidence of recurrent furunculosis and its anaerobic etiology. Results: Between Jan 2006 and Nov 2016 we identified 41.76% case of recurrent furunculosis. Within this group aerobes were isolated in 29.53% cases, anaerobes were in 53.60% and fungus was in 16.87%. The genus Fusobacterium neucleatum (28.7%) predominates among anaerobes. Conclusion: This study emphasizes that anaerobes have their own importance in the cases of recurrent furunculosis.